A Clinicopathological Investigation of White Matter Hyperintensities and Alzheimer’s Disease Neuropathology - Alosco, Michael L. (J Alzheimers Dis, 2018)
BACKGROUND: White matter hyperintensities (WMH) on magnetic resonance imaging have been postulated to be a core feature of Alzheimer’s disease. Clinicopathological studies are needed to elucidate and confirm this possibility. OBJECTIVE: This study examined: 1) the association between ante-mortem WMH and autopsy-confirmed Alzheimer’s disease neuropathology (ADNP), 2) the relationship between WMH and dementia in participants with ADNP, and 3) the relationships among cerebrovascular disease, WMH and ADNP. METHODS: The sample included 82 participants from the National Alzheimer’s Coordinating Center’s Data Sets who had quantitated volume of WMH from ante-mortem FLAIR MRI and available neuropathological data. The Clinical Dementia Rating (CDR) scale (from MRI visit) operationalized dementia status. ADNP+ was defined by moderate to frequent neuritic plaques and Braak stage III-VI at autopsy. Cerebrovascular disease neuropathology included infarcts or lacunes, microinfarcts, arteriolosclerosis, atherosclerosis, and cerebral amyloid angiopathy. RESULTS: 60/82 participants were ADNP+. Greater volume of WMH predicted increased odds for ADNP (p=0.037). In ADNP+ participants, greater WMH corresponded with increased odds for dementia (CDR≥1; p=0.038). WMH predicted cerebral amyloid angiopathy, microinfarcts, infarcts and lacunes (p’s<0.04). ADNP+ participants were more likely to have moderate-severe arteriolosclerosis and cerebral amyloid angiopathy compared to ADNP− participants (p’s<0.04). CONCLUSIONS: This study found a direct association between total volume of WMH and increased odds for having ADNP. In patients with Alzheimer’s disease, FLAIR MRI WMH may be able to provide key insight into disease severity and progression. The association between WMH and ADNP may be explained by underlying cerebrovascular disease.